2014
DOI: 10.1080/01621459.2013.869224
|View full text |Cite
|
Sign up to set email alerts
|

Convex Optimization, Shape Constraints, Compound Decisions, and Empirical Bayes Rules

Abstract: Abstract. Estimation of mixture densities for the classical Gaussian compound decision problem and their associated (empirical) Bayes rules is considered from two new perspectives. The first, motivated by Brown and Greenshtein (2009), introduces a nonparametric maximum likelihood estimator of the mixture density subject to a monotonicity constraint on the resulting Bayes rule. The second, motivated by Jiang and Zhang (2009), proposes a new approach to computing the Kiefer-Wolfowitz nonparametric maximum likeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
261
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 159 publications
(267 citation statements)
references
References 29 publications
6
261
0
Order By: Relevance
“…The latter failing can be addressed by a further monotonization step, or by a penalization approach as suggested in Koenker and Mizera (2014). However, a more direct approach is possible via the Kiefer-Wolfowitz non-parametric maximum likelihood estimator (KWMLE) for the mixture model.…”
Section: Empirical Bayes: a Brief Overviewmentioning
confidence: 99%
“…The latter failing can be addressed by a further monotonization step, or by a penalization approach as suggested in Koenker and Mizera (2014). However, a more direct approach is possible via the Kiefer-Wolfowitz non-parametric maximum likelihood estimator (KWMLE) for the mixture model.…”
Section: Empirical Bayes: a Brief Overviewmentioning
confidence: 99%
“…Implementations of all the procedures described here are available in the R package REBayes, Koenker (2012). For further details on computational aspects see Koenker and Mizera (2014).…”
Section: Empirical Bayes and The Kiefer-wolfowitz Mlementioning
confidence: 99%
“…The main drawback of this proposal was the painfully slow convergence of the fixed point iteration of the EM algorithm used to compute the NPMLE. Koenker and Mizera (2014b), observing that the discretization suggested by Jiang and Zhang (2009) produced a convenient, finite dimensional convex optimization problem showed that the NPMLE could be implemented much more efficiently by standard interior point methods.…”
Section: Introductionmentioning
confidence: 99%
“…Mixture models have played a central role in this revival, and this has sparked renewed interest in the Kiefer and Wolfowitz (1956) nonparametric maximum likelihood estimator (NPMLE) for mixtures. Relatively recent developments in convex optimization have dramatically improved computational methods for the Kiefer-Wolfowitz NPMLE, as described in Koenker and Mizera (2014b). To make these methods accessible to the research community we have developed an R package REBayes (Koenker 2017) that incorporates a wide variety of nonparametric mixture models and provides Kiefer-Wolfowitz procedures for each of them.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation